Deficit-Based Indigenous Health Research and the Stereotyping of Indigenous Peoples - Hyett, Sarah Louise; Gabel, Chelsea; Marjerrison, Stacey; Schwartz, Lisa (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2019)
Health research tends to be deficit-based by nature; as researchers we typically quantify or qualify absence of health markers or presence of illness. This can create a narrative with far reaching effects for communities already subject to stigmatization. In the context of Indigenous health research, a deficit-based discourse has the potential to contribute to stereotyping and marginalization of Indigenous Peoples in wider society. This is especially true when researchers fail to explore the roots of health deficits, namely colonization, Westernization, and intergenerational trauma, risking conflation of complex health challenges with inherent Indigenous characteristics. In this paper we explore the incompatibility of deficit-based research with principles from several ethical frameworks including the Tri-Council Policy Statement (TCPS2) Chapter 9, OCAP® (ownership, control, access, possession), Inuit Tapiriit Kanatami National Inuit Strategy on Research, and Canadian Coalition for Global Health Research (CCGHR) Principles for Global Health Research. Additionally we draw upon cases of deficit-based research and stereotyping in healthcare, in order to identify how this relates to epistemic injustice and explore alternative approaches.